The Impact of Palm Oil Plantations on Per Capita Income in Kalimantan and Its Effect on Unemployment - Januar Barkah; Sumaryoto Sumaryoto; Muhammad Rozali (CV. Syntax Corporation Indonesia, 2024)
Currently, Indonesia's oil palm plantation sector is in a critical phase. While the sector has contributed significantly to national income and created jobs, it is increasingly urged to address a number of social and environmental issues. This study aims to explain the complex relationship between oil palm plantation expansion, per capita income, and unemployment dynamics in the region. Using quantitative methodology and multiple linear regression analysis, this study examines secondary data sourced from the Central Bureau of Statistics (BPS) and the Ministry of Agriculture covering the period 2001-2022. The findings show that the expansion of oil palm plantations significantly increases per capita income through direct and indirect job creation. However, its impact on unemployment is not uniform and depends on the prevailing economic structure and adaptability of the local labor market. While some regions experienced a decline in unemployment due to increased job availability, other regions experienced an increase in structural unemployment caused by the adoption of modern technology that reduced the need for manual labor. These findings underscore the need for regional policies tailored to the local economic context, labor market, and local employment conditions